2021
DOI: 10.1186/s12905-021-01274-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health disparities in breast cancer incidence burden in Tennessee: geospatial analysis

Abstract: Background Tennessee women experience the 12th highest breast cancer mortality in the United States. We examined the geographic differences in breast cancer incidence in Tennessee between Appalachian and non-Appalachian counties from 2005 to 2015. Methods We used ArcGIS 10.7 geospatial analysis and logistic regression on the Tennessee Cancer Registry incidence data for adult women aged ≥ 18 years (N = 59,287) who were diagnosed with breast cancer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…This finding aligns with a recently published study that investigated geographic differences in late stage BC diagnosis in Tennessee. 27 However, the study also found that of the 9 Tennessee counties with the highest incidence rates, six fall within Appalachia. 27 …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This finding aligns with a recently published study that investigated geographic differences in late stage BC diagnosis in Tennessee. 27 However, the study also found that of the 9 Tennessee counties with the highest incidence rates, six fall within Appalachia. 27 …”
Section: Discussionmentioning
confidence: 85%
“… 27 However, the study also found that of the 9 Tennessee counties with the highest incidence rates, six fall within Appalachia. 27 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This reverse association may be unique to pre-treatment because of anticipatory anxiety of the unknown treatment process, and marital quality could be linked to lower distress during treatment, as evidenced in other research. 3,11,34 However, such a reverse effect does expand the BBFM hypotheses to include how the effect of perceived threats to the relationship may trigger BBR dysregulation differently.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the leading cancer diagnosed among US women, 1 with most (80%) having Estrogen Receptor Positive (ER+) tumors 2 . However, for the 2.9 million people living in East Tennessee (the Appalachian region of the state), the incidence of breast cancer is almost two times higher, 3 with significantly worse survival rates 4 . During breast cancer treatment—which can include surgery, chemotherapy, radiation, or adjuvant endocrine therapy, patients and their caregivers (e.g., family member, spouse, friend) often experience increased biobehavioral reactivity, which includes psychological (e.g., depressed mood) and physiological (e.g., pain, fatigue) dysregulation symptoms 5–7 .…”
Section: Introductionmentioning
confidence: 99%